2017
DOI: 10.1021/acs.jced.6b00660
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Properties and Absorption Mechanism Investigation of Dilute SO2 in Propylene Glycol Monomethyl Ether + Dimethyl Sulfoxide System

Abstract: In this work, the propylene glycol monomethyl ether (PGME) + dimethyl sulfoxide (DMSO) system was used in absorption process of SO 2 , and the gas−liquid equilibrium (GLE) data of SO 2 in the PGME + DMSO system were determined at T = 298.15, 303.15, and 308.15 K and p = 123.15 kPa. The experimental data are used to develop SO 2 solubility model, which shows a potential application for SO 2 removal. After that, Henry's law constants (HLCs) were calculated by fitting the linear slope of solubility, and thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The asymmetry stretching vibration peaks of SO 2 appeared at 1323 cm −1 in the rich MDEA+DMSO solution, 61 which indicated some captured SO 2 molecules maintained their intrinsic structure due to the interaction between DMSO and SO 2 (Figure 9). Meanwhile, the stretching vibrational peak of S=O in MDEA+DMSO shifted from 1079 to 1076 cm −1 after absorption and displaced to 1079 cm −1 after desorption.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…The asymmetry stretching vibration peaks of SO 2 appeared at 1323 cm −1 in the rich MDEA+DMSO solution, 61 which indicated some captured SO 2 molecules maintained their intrinsic structure due to the interaction between DMSO and SO 2 (Figure 9). Meanwhile, the stretching vibrational peak of S=O in MDEA+DMSO shifted from 1079 to 1076 cm −1 after absorption and displaced to 1079 cm −1 after desorption.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…In addition, a series of byproducts and wasted water are produced. Other methods mainly include organic solvents absorption and ammonia scrubbing, whereas the solvents volatilization cannot be neglected. Therefore, it is highly desired to develop the efficient, green, and reversible absorbents for flue gas desulfurization (FGD).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the FTIR spectrum of the virgin absorbent, three characteristic peaks of absorbed SO 2 appeared after absorption. The new peak centered at 956 cm –1 could be attributed to the stretching vibration of S–O bonds in SO 3 2– or HSO 3 – , which indicated that the studied absorbent could capture SO 2 via chemical interaction. , The new peak at 1046 cm –1 could be assigned to the SO stretching vibration of SO 2 , H 2 SO 3 , HSO 3 – , or SO 3 2– . , The characteristic peak presented at 1328 cm –1 was ascribed to the asymmetry stretching vibration of dissolved SO 2 . , Additionally, it was clear that captured SO 2 presented a significant effect on −COOH and −COO – in aq. More concretely, the symmetric (1562 cm –1 ) and asymmetric (1383 cm –1 ) vibrations of −COO – were weakened gradually during SO 2 absorption, whereas the vibrations (1712 and 1627 cm –1 ) associated with −COOH were enhanced notably, implying that −COOH was formed during the absorption process. ,, Meanwhile, in comparison to the 1 H NMR spectrum (Figure S1 of the Supporting Information) of the virgin absorbent, the spectrum of the 0.2 vol % SO 2 saturated absorbent presented a new peak at 9.97 ppm, which could be assigned to the H atom bonded to the N atom of [DMEDA] + , , demonstrating that [DMEDA] + also played an important role in SO 2 capture.…”
Section: Results and Discussionmentioning
confidence: 88%
“…40,41 The characteristic peak presented at 1328 cm −1 was ascribed to the asymmetry stretching vibration of dissolved SO 2 . 42,43 Additionally, it was clear that captured SO 2 presented a significant effect on −COOH and −COO − in aq. More concretely, the symmetric (1562 cm −1 ) and asymmetric (1383 cm −1 ) vibrations of −COO − were weakened gradually during SO 2 absorption, whereas the vibrations (1712 and 1627 cm −1 ) associated with −COOH were enhanced notably, implying that −COOH was formed during the absorption process.…”
Section: Methodsmentioning
confidence: 97%